The Intervention Strategies To Reduce Tuberculosis Stigma Based On Community: A Systematic Review - Mulyana, Rezky; Nursasi, Astuti Yuni (Universitas Pendidikan Indonesia, 2019)
ABSTRACTStigma in tuberculosis patients causes discrimination and social isolation that have an impact on efforts to manage tuberculosis treatment. The purpose of this review is to explore based community intervention strategies to reduce tuberculosis (TB) stigma. Method: The design applied systematic review. Data was retrieved from online database Wiley Online Library, Science Direct, PubMed, Research Gate, Springer Link, Scopus, Google Scholar, and national journal in the period of 2008-2018. The study selection was conducted in the search string by applying the keywords â€œTBâ€ AND â€œStigmaâ€, â€œReduce stigmaâ€, â€œIntervention TB Stigmaâ€, â€œtackling stigma TBâ€, â€œstrategy for TB stigmaâ€, exploration and selection of title, abstract were conducted inclusion criteria, and search the articles by screening reference lists in citations in the literature to be additional articles. Analysis result of study uses PRISMA flow diagram. Results: The intervention strategies to reduce TB stigma reviewed from articles and found 4 intervention strategies are: (1) Health education, such as knowledge shipping about TB and TB Campaigns, (2) Home Visit, (3) TB Patients support such as Community, family support, social support TB Club, and financial support, (4) Enhancing Qualities of health worker. Conclusions: The intervention strategies to reduce TB stigma are needed in reducing TB stigma. Low TB stigma has positive effect in controlling and eliminating TB. The most common intervention are TB patient support and health education.ABSTRAKStigma pada pasien tuberkulosis (TB) menyebabkan diskriminasi dan isolasi sosial yang berdampak pada upaya manajemen pengobatan TB. Tujuan dari literatur review ini untuk mengeksplorasi strategi intervensi di komunitas untuk mengurangi stigma tuberkulosis (TB). Desain menerapkan tinjauan sistematis. Data diambil dari database online Wiley Online Library, Science Direct, PubMed, Research Gate, Springer Link, Scopus, Google Cendekia, dan jurnal nasional pada periode 2008-2018. Pencarian artikel dalam sistematik review ini menerapkan kata kunci